2001
DOI: 10.1023/a:1021224915322
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Strains of Escherichia coli, hybridising with a DNA probe for enteroaggregative E. coli (EAggEC), were isolated from patients with infectious intestinal disease (IID) or gastro-enteritis, and healthy controls during the study of IID in England. Of 3506 cases presenting with an IID, 160 (4.6%) had faecal EAggEC as compared with 46 (1.7%) of 2772 healthy controls, 53% of EAggEC isolated from each of the 'case' and the 'control' groups adhered in a 'stacked-brick' formation. Strains from cases and controls belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…Indeed, two large prospective surveillance studies in the UK and USA identified EAEC amongst the most commonly isolated bacterial species from individuals with diarrhea, with isolation rates similar to Campylobacter jejuni and greater than Salmonella sp. [8], [9]. Furthermore, a meta-analysis of the previously published case control studies from a variety of different geographical regions clearly supports a role for EAEC in mediating diarrheal disease, and the increasing number of reports in which EAEC is implicated as the agent mediating diarrhea suggest that this is an important emerging pathogen [10].…”
Section: Introductionmentioning
confidence: 72%
“…Indeed, two large prospective surveillance studies in the UK and USA identified EAEC amongst the most commonly isolated bacterial species from individuals with diarrhea, with isolation rates similar to Campylobacter jejuni and greater than Salmonella sp. [8], [9]. Furthermore, a meta-analysis of the previously published case control studies from a variety of different geographical regions clearly supports a role for EAEC in mediating diarrheal disease, and the increasing number of reports in which EAEC is implicated as the agent mediating diarrhea suggest that this is an important emerging pathogen [10].…”
Section: Introductionmentioning
confidence: 72%
“…Hwoever, it was not possible to compare the serotypes isolates following the outbreak with the serotypes of strains of EAEC currently circulating in England as there are very little data on domestically acquired strains of EAEC. Surveillance data indicates that the majority of strains of EAEC isolate in England are from cases of travellers' diarrhoea [12], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Two independent, large, prospective studies of diarrhoea aetiology conducted in the UK (1993–1996) and USA (2002–2004) reported a similar EAEC prevalence in patients with diarrhoea: 4.6% (160/3506) and 4.5% (37/823) in the UK and US studies, respectively, and 1.7% in control subjects from both studies [11], [12]. Clinical symptoms include watery diarrhoea, often with mucus, low grade fever, abdominal pain, nausea and vomiting [10].…”
Section: Introductionmentioning
confidence: 88%
“…However, it is worth recalling many studies have demonstrated the presence of EAEC strains in healthy controls (ca. 2%) and that the rate of recovery of EAEC in symptomatic individuals is approximately 3-fold higher [44], [45]. Therefore, a simplistic hypothesis would suggest that approximately one third of the strains isolated from symptomatic individuals are not associated with disease but simply part of the resident commensal flora.…”
Section: Discussionmentioning
confidence: 99%